Theoretical investigation on the electronic structures and phosphorescent properties of a series of cyclometalated platinum(II) complexes with different substituted N-heterocyclic carbene ligands. (22nd January 2016) - Han, Deming; He, Xiuxia; Zhao, Lihui; Pang, Chunying; Yu, Yuanhua; Zhang, Gang
ABSTRACT: A series of substituted platinum(II) complexes with a chelating N-heterocyclic carbene (NHC) ligand and a bidentate monoanionic auxiliary ligand (acetylacetone) have been investigated by using the density functional theory (DFT) and time-dependent density functional theory (TDDFT) methods, to explore their electronic structures, absorption and emission properties, and phosphorescence quantum efficiency. The influence of different substituted groups on photophysical properties of complexes studied has been detailedly analyzed. The lowest energy absorption and emission wavelengths calculated are comparable to the available experimental values. In addition, ionization potential (IP), electron affinities (EA), and reorganization energy (λ) were obtained to evaluate the charge transfer and balance properties between hole and electron. The calculated results also show that, due to a lower, larger 3 MLCT contribution, and higher value, the complex5 owns possibly the largest k r value among these complexes. The theoretical studies could provide useful information for the candidated phosphorescent platinum(II) material for use in the organic light-emitting diodes.